Clinical features, diagnosis and treatment outcome of fungal endocarditis: A systematic review of reported cases. Issue 3 (3rd December 2021) - Meena, Durga Shankar; Kumar, Deepak; Agarwal, Madhulata; Bohra, Gopal Krishana; Choudhary, Rahul; Samantaray, Subhashree; Sharma, Shivang; Midha, Naresh; Garg, Mahendra Kumar
Abstract: The landscape of fungal endocarditis (FE) has constantly been evolving in the last few decades. Despite the advancement in diagnostic methods and the introduction of newer antifungals, mortality remains high in FE. This systematic review aimed to evaluate the epidemiology, clinical features, diagnostic and therapeutic interventions in patients with FE. We also aim to examine the aforementioned factors as a determinant of mortality in FE. A literature search was performed in PubMed, Google Scholar and Scopus, and all patients ≥18 years with proven fungal endocarditis were included. A total of 220 articles (250 patients) were included in the final analysis. Candida was the commonest aetiology (49.6%), followed by Aspergillus (30%) and Scedosporium species (3.2%). The proportion of prosthetic valve endocarditis (PVE) and intravenous drug users was 35.2% and 16%, respectively. The overall mortality rate was 40%. On multivariate analysis, Aspergillus endocarditis (HR 3.7, 95% CI 1.4‐9.7; p = .009) and immunocompromised state (HR 2.8, 95% CI 1.24‐6.3; p = .013) were independently associated with mortality. Patients treated with surgery along antifungals had better survival (HR 0.20, 95% CI 0.09‐0.42; p < .001) compared to those treated with antifungals alone. Recurrence of FE was reported in 10.4% of patients. In conclusion, FE carries significant mortality, particularly in immunodeficient and Aspergillus endocarditis. We advocate the use of surgery combined with antifungals to improve clinical outcomes.